O skupinskem in snovalnem ustvarjanju v slovenskem gledališču - Milohnić, Aldo (Amfiteater (Ljubljana), 2021)
In the first part of the article, the author analyses the appearance of the director and the changes in his position in Slovenian theatre from the second half of the 19th century to the present day. In this context, he is particularly interested in the changes in theatre directing that took place in the second half of the 20th century with the emergence of collective theatre. The author methodologically combines historical and comparative analysis, as these processes still take place today, when devised theatre and other forms of theatrical creation are increasingly spoken and written about, moving away from the conventional process by which a playwright writes a dramatic text as a literary work of art and the director then transforms it into a theatrical work of art. There are more and more performances in contemporary Slovenian theatre in which a pre-written dramatic text is not crucial for the final product of the creative process. The two most commonly used terms for this type of performance are po motivih (based on the motifs) and avtorski projekt (auteur performance). Although the terms are not synonymous, both terms imply a devised type of theatre. The author compares group creation with the devised way of creating and points out that although these are practices that can take place in parallel, they cannot be equated. The author concludes that for collective theatre, the specific relationship between the creative group and the director's position is constitutive. In contrast, for devised theatre, the relationship between the creative group and the playwright's position is crucial. Finally, the author also touches on the connections between postdramatic and post-directors' theatre and the emergence of the creative group as a collective subjectivity.
Keywords: collective creation; devised theatre; directors' theatre; eksperimentalno gledališče; experimental theatre; post-directors' theatre; postrežijsko gledališče; režijsko gledališče; skupinsko ustvarjanje; Slovenian theatre; slovensko gledališče; snovalno gledališče